Pemetaan Penelitian Seputar Kualitas Audit : Analisis Bibliometrik Vosviewer - Auria Revi Marisa; Ahmad Fahrudin Alamsyah; Sri Andriani (AKUNTANSI 45, 2024)
This study was studied to analyze research maps related to Quality Audit with bibliometric Vosviewer studies. The techniques used in reviewing the data in this study are: (1) in a span of 10 years starting from 2014 to 2024 by utilizing the Publish or Perish application through google schoolar which uses the keyword Audit Quality with a result of 500. (2) Sorting out the metadata of the article in accordance with the criteria to be researched through the help of Mendeley. (3) Map the results of the VOSViewer bibliometric visualization related to Quality Audit by grouping based on the number of clusters and items. The results show that the number of publications about Audit Quality is divided into 3 clusters and 50 topic items related to Audit Quality. The involvement and role of this research is to visualize the main points of research related to Quality Audit. The results of this visualization can be used as a reference for the next researcher to carry out further research.